Exogenous cystine increases susceptibility of drug-resistant Salmonella to gentamicin by promoting oxidation of glutathione metabolism and imbalance of intracellular redox levels - Du, Junyuan; Wu, Zhiyi; Zhu, Chunyang; Yang, Heng; Zhao, Feike; Fang, Binghu (Frontiers in Microbiology, 2025)
IntroductionAntibiotic overuse has caused the development of bacterial resistance, which is a major threat to public health. Intracellular metabolic processes are essential for maintaining the normal physiological activities of bacteria, and an increasing body of research has demonstrated a significant association between metabolic alterations and the development of drug resistance. Numerous studies have demonstrated that the addition of adjuvants can counteract bacterial antibiotic resistance.MethodCystine treatment was verified in vitro to promote the lethal effect of gentamicin on Salmonella using in vitro bactericidal counting methods. The metabolic differences in Salmonella enterica Typhimurium standard strain ATCC 14028 with or without the addition of cystine were analyzed via untargeted metabolomics. The multifunctional electronic enzyme marker was used to determine intracellular reduced glutathione/oxidized glutathione (GSH/GSSG), ferrous iron on (Fe2+), and reactive oxygen species (ROS) levels. The expression of glutathione and stress genes was determined using real-time quantitative PCR.ResultWe confirmed that exogenous cystine increased the lethal effect of gentamicin against strain S. enterica Typhimurium (ATCC 14028) and other clinically resistant Salmonella serotypes. Exogenous cystine stimulated the metabolism of the cell and activated the glutathione pathway while altering the GSH/GSSG ratio, which placed bacteria in a state of redox imbalance with increased Fe2+ and ROS levels. Our results suggest that when bacterial redox levels are reprogrammed, bacterial susceptibility to antibiotics can also change.DiscussionThis study confirms that cystine enhances the antimicrobial efficacy of gentamicin against drug-resistant Salmonella. Through the application of metabolomics, the underlying metabolic mechanisms by which cystine exerts its effects on Salmonella have been elucidated, offering a novel perspective in the domain of metabolic reprogramming aimed at counteracting drug resistance. Furthermore, these findings reinforce the potential role of small-molecule metabolites as effective adjuvants to enhance antibiotic action.